Neutralizing Acid Mine Drainage (AMD) and Reducing Iron (Fe) and Copper (Cu) Content Using Biomass Adsorbents - Hendriono, Hendriono; Cahyadi, Tedy Agung; Ernawati, Rika (Journal of Earth and Marine Technology (JEMT), 2025)
Mining is an activity that always has an impact on the environment. The adverse effects that cannot be separated from the mining process are mined acid water, where the process of mining acid water occurs due to contact between sulfide rocks and air or water; environmental pollution by mined acid water must be overcome immediately, in the prevention of ecological damage by mine acid water, Various methods are carried out to reduce the impact of mine acid water pollution, one example of a technique that is often used is with limestone channels, where the gaps are filled with limestone fragments to neutralize mine acid water, The method used in this study is an experimental design with an adsorption process. The data collection method in the study uses literature studies, field observations, research preparations, rice husk preparation, coconut coir, and fine coal, Acid Water samples are taken and brought for the testing process. The test results using a pH meter at the Yogyakarta Center for Environmental Health and Disease Control Engineering (BBTKLPP) showed that the pH of AAT was 3.8. Based on the results of the AAS test at BBTKLPP Yogyakarta, the AAT sample contained Fe metal of 130.56 mg/L and Cu of 2.96 mg/L. The highest adsorption effectiveness was in a 3x24 hour adsorbent experiment with a period of 50 grams with a time of pH 45.71%, Fe 98.90%, and Cu 98.71%.